A design-thinking perspective on capability development: The case of new product development for a service business model. Issue 4 (20th February 2018) - Beltagui, Ahmad
Abstract : Purpose: The purpose of this paper is to examine the interaction between new product development (NPD) capabilities and business model innovation (BMI) by studying the adaptation of capabilities in a manufacturing firm as it adopts a service business model. Design/methodology/approach: An in-depth case study is used to identify design capabilities and document how these have been developed as the firm has adapted its NPD processes to the needs of its service business model. Findings: Design capabilities are proposed as a facilitator of servitization, allowing a manufacturing firm to develop service offerings that build on resources such as knowledge and experience. Conversely, the scope of servitization is restricted by the extent to which these design capabilities can be updated to suit the demands of a new business model. Practical implications: Servitization is presented as an imperative for manufacturing firms, yet research has not addressed the implications for NPD nor investigated how BMI affects NPD capabilities. This study shows the need to identify whether current NPD processes help or hinder BMI and proposes how managers can adapt NPD processes to a new business model. Originality/value: A three-stage process is identified for adapting NPD processes – as BMI changes the nature of products and services required, existing processes are supplemented by design activities requiring expert knowledge, these are subsequently refined into design methods that can be incorporated into the NPD process, and eventually design tools allow automation and efficiency.